Abdominoplasty in a patient after bariatric surgery – case study - Flis, Blanka; Niekurzak, Karolina; Jędrak, Maciej; Józefiak, Maciej; Sobkiewicz, Piotr (Quality in Sport, 2024)
Introduction: Up to 96% of patients after bariatric surgery struggle with excess skin, which negatively affects their daily functioning due to frequent skin infections, difficulties with sexual activity and physical exercise, as well as discomfort, especially in social situations. Abdominoplasty is a surgical procedure that allows post-bariatric patients to resolve these problems. At the same time, like any surgical intervention, the incidence of complications is relatively low. These potential complications after surgery include mainly superficial wound dehiscence or other minor complications. Purpose of the work: This study aims to detail the stages of abdominoplasty performed on a post-bariatric surgery patient and to demonstrate the outcomes achieved. Materials and methods: In this study, the individual case study method was used. The subject of the study was a 36-year-old woman after bariatric surgery who, having lost more than fifty kilograms and already having a normal BMI= 23.88 kg/m², applied for an abdominoplasty procedure. For practical reasons, despite indications for a circular abdominoplasty, the patient underwent a classic abdominoplasty complemented by liposuction. Results: During the abdominoplasty procedure, liposuction of the lateral fat tissue was performed, along with the removal of a skin-fat fold weighing over 1 kilogram, reinforcement of the abdominal muscles, and repositioning of the navel. The patient left the clinic without any drainage in place. After 8 days, the sutures placed during the operation were removed and after 4 weeks, the effects of the surgery were also verified by photo documentation. The abdominoplasty performed in the post-bariatric patient allowed for the successful removal of the excess skin after a considerable amount of weight loss. The procedure required meticulous planning and adaptation of surgical methods and techniques to the patient’s living situation.